Corrosion mechanism of a high corrosion-resistance Zn–Al–Mg coating in typical extremely harsh marine and cold environments - Yuwei Liu; Tianzhen Gu; Miaoran Liu; Zhenyao Wang; Gongwang Cao; Quanzhong Guo; Chuan Wang (Journal of Materials Research and Technology)
The corrosion mechanism of a high corrosion-resistant Zn–Al–Mg coating exposed to typical extremely harsh environments in Wanning and Mohe was investigated. The findings revealed that the corrosion behavior of Zn–Al–Mg coating is significantly influenced by environmental conditions, exhibiting varying rates and processes in high-temperature marine and extremely cold urban environments, which lead to distinct corrosion patterns and pit morphologies over time. In the marine atmosphere of Wanning, characterized by high temperature and humidity, corrosion preferentially occurs in the eutectic phase and extends towards the interior of the coating along the eutectic phase near the zinc-rich phase. The corrosion rate on the skyward side is smaller than that on the field-facing side, and this difference between the two sides initially decreases and later increases. However, in the urban atmosphere of Mohe, with extremely low temperatures, the phenomenon of localized corrosion is more pronounced. Corrosion pits tend to form in the eutectic phase near the zinc-rich phase, with their shapes gradually transitioning from sharp to shallow. After 6 and 12 months of exposure, the corrosion rate on the skyward side is smaller than that on the field-facing side, and after 24 months of exposure, both sides exhibit similar corrosion rates.